EXPLORING PEKALONGAN BATIK MOTIFS AS GEOMETRY LEARNING MATERIALS FOR ELEMENTARY SCHOOL STUDENTS - Sofliatin, Uswatul Khasanah; Fiantika, Feny Rita; Rusminati, Susi Hermin (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
This research aims to develop ethnomathematics-based teaching materials on shapes for 3rd-grade elementary school students. The research method used is Thiagarajan’s 4D development model, which consists of four stages: Define, Design, Development, and Disseminate. In the define stage, initial-final analysis, task analysis, concept analysis, and learning objective analysis were conducted. The design stage involves systematically organizing the content framework of the teaching materials, including the initial draft, format selection, and preparation of the teaching materials, resulting in the first draft. Validation assessments by experts and student response questionnaires were also conducted at this stage. The development stage involves creating ethnomathematics-based teaching materials, which mathematics experts evaluate. After obtaining validation assessments, the teaching materials were tested on 26 students of the 3rd-grade elementary school. The results of the validation by experts indicate that these teaching materials have a very high feasibility level. The students’ responses also showed that the teaching materials are very suitable. The dissemination stage involves distributing these teaching materials to more schools to gain broader feedback. Overall, the ethnomathematics-based teaching materials developed in this study are feasible and effective for teaching mathematics in 3rd-grade elementary schools. This research demonstrates excellent potential for enhancing students’ understanding of two-dimensional figure concepts through an ethnomathematics approach. This approach connects mathematics with local culture, making learning more relevant and engaging